P284 Assessment of prothrombotic tendency in IBD pregnant patients and its associated risk factors. (25th January 2019) - Rottenstreich, A; Diminsky, M; Grisaru-Granovsky, S; Tali, M; Roth, B; Spectre, G; Kalish, J; Abitbol, G; Hoyda, A; Goldin, E; Bar-Gil Shitrit, A
Abstract: Background: Inflammatory bowel diseases (IBD) are an established risk factor for thrombotic complications. IBD pregnant patients are at even greater risk for thrombosis. Nevertheless, the risk factors associated with this prothrombotic tendency among IBD parturient are not well-established. The objective of our study was to examine the characteristics associated with hypercoagulability in pregnant women with IBD. Methods: A prospective cohort study, performed during 2017–2018 at a university hospital, of women attending a specialised, multi-disciplinary clinic for the preconception, antenatal and postnatal treatment of IBD women. Women were consecutively recruited and tested for thrombin generation, a global marker of the coagulation system, expressed as the endogenous thrombin potential (ETP). Results: One hundred and forty-five women with IBD were enrolled in this study; 100 had Crohn's disease, 43 ulcerative colitis and 2 indeterminate colitis. The median age of this cohort was 29 [26–33] years. In univariate analysis that included all measured clinical and laboratory parameters, ETP levels were directly correlated with duration of pregnancy ( p < 0.0001), disease activity as assessed by physician global assessment ( p = 0.005), extra-intestinal involvement ( p = 0.04), C-reactive protein level ( p < 0.0001), erythrocyte sedimentation rate ( p < 0.0001), white blood cell count ( p = 0.008), body mass index ( p = 0.02) and inversely correlated with haemoglobin level ( p < 0.0001). ETP level did not correlate with any of the other clinical and laboratory characteristics assessed. In multi-variate analysis, duration of pregnancy ( p < 0.0001), active disease ( p = 0.009), extra-intestinal involvement ( p = 0.02) and body mass index ( p = 0.05) were the only independent predictors of ETP level. Conclusions: As determined by thrombin generation, IBD pregnant patients have an enhanced procoagulant potential which increased throughout gestation. This enhanced hypercoagulability was independently associated with disease activity, body mass index, and the presence of extra-intestinal disease involvement. Future prospective studies are warranted to confirm our findings and better delineate the optimal antithrombotic prophylactic strategy in this setting